The Influence of Mother's Education Level on Child Development: A Meta-Analysis Study - Tampubolon, Aptylia Naomi; Ingtyas , Fatma Tresno; Ginting , Laurena (CV. Tripe Konsultan, 2024)
This study analyzes the influence of maternal education level on child development, focusing on nutritional status, motor development, and child health. Based on a review of 15 relevant journals, it was found that mothers with higher education levels have better knowledge about nutrition, developmental stimulation, and the importance of immunization, which contributes to more optimal child growth. Conversely, mothers with lower education levels often lack knowledge about healthy eating and disease prevention, which increases the risk of child health issues, such as stunting. Additionally, family economic factors also affect the mother's ability to apply that knowledge. Overall, the increase in maternal education has a positive impact on the quality of children's health and development, which can help reduce the prevalence of nutritional problems and stunting.